Straits Settlements Blue Book (imports/exports) 1913-1914 vol.60-61 (Great Britain : Public Record Office, 1971)
Mengandungi sambungan :Straits Settlements return if imports and exports during the year 1913';'Statement of the quantities and value of imports and exports of the colony of the Straits Settlements from and to other Countries in 1912 and 1913';'Blue Book for the year 1914'.